Effects of Buffers and pH on the Reaction of a trans‐Platinum Complex with 5′‐Guanosine Monophosphate1. Issue 29 (11th September 2015) - Li, Chan; Ding, Yi; Cheng, Lanjun; Zheng, Yuchuan; Sletten, Einar; Liu, Yangzhong
Abstract: The aquation of platinum anticancer drugs is a crucial step for their activation and the consequent binding to the target DNA. These processes can be influenced by small molecules, such as carbonate and phosphate, which are present in high concentration in physiological conditions. In this work, the effects of buffer and pH on the reaction of trans‐EE trans ‐[PtCl2 E ‐HN=C(OCH3 )CH3 2 ] with 5′‐guanosine monophosphate (5′‐GMP) have been studied in detail. The reactions were monitored by HPLC at different pH in the presence of carbonate, phosphate, and HEPES [4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid] buffers. trans‐EE showed a very low affinity for the nitrogen atoms of HEPES, but formed monofunctional adducts with carbonate and phosphate ions. The platination of GMP by trans‐EE was significantly affected by the choice of buffer and pH. Carbonate buffer decreased the reaction rate, mostly due to its competition with GMP. Although phosphate buffer formed a similar monofunctional adduct with trans‐EE, it had a negligible effect on the platination rate of GMP. This may be due to the formation of ternary adducts with trans‐EE and GMP. In all cases, the platination reaction was slower at higher pH, probably due to the deprotonation of an aqua ligand on the mono‐aqua complex of trans‐EE . The results in this paper indicate that the solution conditions have a different effect on the reaction of trans ‐platinum complexes compared with cisplatin. Abstract : The reaction of an anti‐tumor trans ‐platinum agent with GMP is influenced by buffer at physiological concentrations. Carbonate buffer reacts with trans‐EE and significantly reduces the platination of GMP, whereas the reaction of phosphate buffer has much less of an effect.